The Dead Sea Genesis Apocryphon : a new text and translation with introduction and special treatment of columns 13-17 - Machiela, Daniel A. (Studies on the Texts of the Desert of Judah, 2009)
The so-called Genesis Apocryphon (1Q20) from Qumran Cave 1 has suffered from decades of neglect, due in large part to its poor state of preservation. As part of a resurgent scholarly interest in the Apocryphon, and its prominent position among the Aramaic Dead Sea Scrolls, this volume presents a fresh transcription, translation, and exstenive textual notes drawing on close study of the original manuscript, all available photographs, and previous publications. In addition, a detailed analysis of columns 13-15 and their relation to the oft-cited parallel in the Book of Jubilees reveals a number of ways in which the two works differ, thereby highlighting several distinctive features of the Genesis Apocryphon. The result is a reliable text edition and a fuller understanding of the message conveyed by this fragmentary but fascinating retelling of Genesis.